A Decade of Science Technology, Engineering, and Mathematics (STEM) Project-Based Learning (PjBL): A Systematic Literature Review - Aprianta Magdalena Simamora (Scientia Publica Media, 2024)
The fields of Science, Technology, engineering, and mathematics (STEM) have advanced significantly in Education. In various research in the world of education, STEM growth is frequently associated with project-based learning (PjBL). Combining STEM learning with PjBL is worth researching. This study’s objective is to comprehensively investigate the link between STEM and PjBL, which covers the most advanced PjBL-STEM idea in academic units, implementation in various nations and educational levels, and the impact of STEM and PjBL relationships on the caliber of students. This analysis identified up to 168 Scopus-recognized papers between 2007 and 2022. This study used a systematic review with a four-step PRISMA-P. Finally, there were 35 articles included in this research. The analysis’s findings demonstrate that STEM PjBL has successfully fostered active learning and student-centered instruction while enhancing 21st-century abilities (creativity, collaboration, problem-solving, creative use of technology, and higher-order thinking). The notion of STEM Subject, or the incorporation of STEM PjBL into activities, is the one that is researched the most in schools. The country that used PjBL STEM learning the most was the United States. In 2018, mixed research methodologies were used to study STEM-PjBL research the most. Secondary education STEM-PjBL studies and teachers are critical for children to become more interested in a STEM profession.